INSPIRACJE GRECKO-RZYMSKIE W IDEOLOGII NAZISTOWSKIEJ - Chiżyńska, Katarzyna (Collectanea Philologica, 2013)
The paper focuses on ancient ideas, myths and texts, which has been adapted by Third Reichin order to build Nazi ideology. Hitler’s followers passionately read works of Plato, Plutarch andTacitus, however, their intention was not to learn about antiquity, but to fit ancient thoughts toNational Socialism. The same thing NSDAP tried to do with ancient art, architecture, gestures(Roman salute) and symbols (swastika). Führer’s attitude towards Greek and Roman antiquity wasvery complex. Psychological term to name this ambiguous relationship is “double-bind”.